Tense and Aspect in the Academic Writing of Arab L2 Learners of English: A Corpus-Based Approach - Mousa A. Btoosh (National Research University Higher School of Economics, 2019)
This study aimed at explicating the use of tense and aspect in the academic writing of Arab L2 learners of English. The scope was restricted to two absolute tenses (simple present and simple past), perfective and imperfective aspects, and verb-form errors arising from the deletion or addition of the third person singular-s besides the omission of copula and auxiliary verbs. The study was conducted on the basis of a comparative, quantitative analysis of the target forms between a learner corpus and a similar-sized native one. In pursuing and achieving the stated objectives, it also concentrated on the types and sources of the tense, aspect and verb form errors in learners' performance. In addition to the significant disparity between the two corpora in terms of the frequency count and percentage of most of the target forms, the findings confirmed learners' tendency to use more verbs than native speakers. Results also showed that learners' use of the preterit (simple past), and perfective and imperfective aspects were largely constrained by their L1 grammar and semantic interpretation of verbs (independent of the target language norm). Moreover, the findings revealed some common inconsistent erroneous forms attributed to the omission or addition of the third person singular-s and the omission of copula and auxiliary verbs. Several main factors were identified as potentially responsible for learners' errors, that is, inconsistency inherent in L2 rules, learners' limited exposure to (authentic) L2, overgeneralization, redundancy reduction, and language transfer. The findings suggest the need to introduce appropriate pedagogical methods to best present the target language rules.